2020
DOI: 10.1111/dth.14387
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with adalimumab biosimilar imraldi in hidradenitis suppurativa

Abstract: Adalimumab is the only biologic therapy approved for the treatment of patients with hidradenitis suppurativa, a chronic and disabling skin condition. To date, there are no studies in the literature about the effectiveness of adalimumab biosimilar SB5 in hidradenitis suppurativa. The aim of this study was to evaluate its efficacy and safety. A retrospective observational study was performed in hidradenitis suppurativa adalimumab naive patients and in patients who were switched from the adalimumab originator. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Ricceri et al evaluated seven HS patients switching adalimumab originator to biosimilar SB5 adalimumab and found similar effectiveness rates compared to naïve HS patients treated with this biosimilar. Nevertheless, tolerability was not evaluated in this report [23]. Patil also reported effectiveness in two HS patients being treated with biosimilar ZRC-3197 adalimumab.…”
Section: Discussionmentioning
confidence: 88%
“…Ricceri et al evaluated seven HS patients switching adalimumab originator to biosimilar SB5 adalimumab and found similar effectiveness rates compared to naïve HS patients treated with this biosimilar. Nevertheless, tolerability was not evaluated in this report [23]. Patil also reported effectiveness in two HS patients being treated with biosimilar ZRC-3197 adalimumab.…”
Section: Discussionmentioning
confidence: 88%
“…At the same time, 6 patients (35.3%) experienced side effects such as pain at the injection site, dizziness and nausea [ 17 ]. One clinical trial observed similar effectiveness and tolerability between originator adalimumab and biosimilar SB5 in 11 patients [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biosimilar ADA (SB5) has also been found to be effective, well tolerated, and interchangeable with originator ADA for HS treatment in a retrospective 36 weeks ‘real life’ observational study. 124…”
Section: Treatmentmentioning
confidence: 99%
“…123 Biosimilar ADA (SB5) has also been found to be effective, well tolerated, and interchangeable with originator ADA for HS treatment in a retrospective 36 weeks 'real life' observational study. 124 Calprotectin, fractalkine, and HCC-4 have been identified as potential predictive biomarkers of ADA response (86% predictive accuracy rate for ADA response). 125 The superior response to TNF-α blockade of subcutaneous nodules versus tunnels suggests that the formation of the latter is mediated by IL-17 rather than by TNF-α signaling.…”
Section: Surgerymentioning
confidence: 99%